LEGAL ANALYSIS OF JUDGES' CONSIDERATIONS IN DECIDING ON CURRICULUM RIGHTS OVER CHILDREN BY THE FORMER WIFE TO THE FORMER HUSBAND ACCORDING TO THE COMPILATION OF ISLAMIC LAW (Decision Study number 155/Pdt.G/2024/PA.Bji) - Sonia Salsabilah; Bambang Fitrianto; Henry aspan (PT. Sinergi Legal Publisher, 2025)
Determination of custody of children under the age of 12 after divorce is usually guided by Article 105 of the Compilation of Islamic Law (KHI), which normatively mandates that child custody be granted to the mother. This research focuses on examining two main issues: the legal factors that influence the determination of child custody rights to the plaintiff, and how the court considers these legal factors in issuing a child custody decision. This research was conducted using a normative legal perspective using qualitative methods, based on an analysis of Decision No. 155/Pdt.G/2024/PA.Bji. The results show that the panel of judges did not adhere strictly to the literal meaning of Article 105 of the KHI, and preferred a more adaptive interpretation, adapting it to concrete conditions in the field. Although both parents are considered capable of caring for the children, the author argues that full custody should still be granted to the mother, considering that the children are still very young and emotionally closer to the mother in their daily lives.